Equal pay law: the state gives with one hand what it takes away with the other (Revista Contexto & Educação, 2025)
Law n. 14.611/2023 (Equal Pay Law) adds to the normative framework aimed at guaranteeing equity and non-discrimination based on gender in the world of work. This paper aims to propose reflections on why such legislation is still necessary, from a critical, feminist, and decolonial perspective. Through a bibliographic review, we aim to problematize its potential reach in the face of a social organization structured in gender and racial coloniality. Initially, we trace a socio-historical contextualization of the sexual division of labor. Then, through legislative analysis, we reflect on the (in)sufficiency of the law, based on Segato's argument (2012) that the State gives with one hand what it takes away with others. Finally, we consider possible paths forward based on the presented debate.
Keywords: Equal Pay Law; Sexual division of labor; Intersectionality